Handbook of research on developments and trends in wireless sensor networks from principle to practice - Jin, Hai; Jiang, Wenbin (Information Science Reference, 2010)
"This book showcases the work many devoted wireless sensor network researchers all over world, and exhibits the up-to-date developments of WSNs from various perspectives"--Provided by publisher.
Keywords: Wireless sensor networks -- Research.; elektronické knihy; electronic books